Regular- and postseason comparisons of playing time and measures of running performance in NCAA Division I women soccer players - Wells, A. J.; Hoffman, J. R.; Beyer, K. S.; Hoffman, M. W.; Jajtner, A. R.; Fukuda, D. H.; Stout, J. R. (Applied Physiology, Nutrition, and Metabolism, 2015)
The management of playing time in National Collegiate Athletic Association (NCAA) soccer athletes may be a key factor affecting running performance during competition. This study compared playing time and running performance between regular-season and postseason competitions during a competitive women`s soccer season. Nine NCAA Division I women soccer players (age, 21.3 ± 0.9 years; height, 170.3 ± 5.7 cm; body mass, 64.0 ± 5.8 kg) were tracked using portable GPS devices across 21 games during a competitive season (regular season (n = 17); postseason (n = 4)). Movements on the field were divided into operationally distinct thresholds defined as standing/transient motion, walking, jogging, low-speed running, moderate-speed running, high-speed running, sprinting, low-intensity running, and high-intensity running. A significant increase in minutes played (+17%, p = 0.010) was observed at postseason compared with the regular season. Concomitant increases in time spent engaged in low-intensity running (LIR: +18%, p = 0.011), standing/transient motion (+35%, p = 0.004), walking (+17%, p = 0.022), distance covered while walking (+14%, p = 0.036), and at low intensity (+11%, p = 0.048) were observed. Performance comparisons between the first and second half within games revealed a significant decrease (p = 0.05) in high-speed and high-intensity runs during the second half of the postseason compared with the regular season. Changes in minutes played correlated significantly with changes in absolute time spent engaged in LIR (r = 0.999, p < 0.001), standing/transient motion (r = 0.791, p = 0.011), walking (r = 0.975, p = 0.001), jogging (r = 0.733, p = 0.025), distance covered while walking (r = 0.898, p < 0.001) and low-intensity activity (r = 0.945, p < 0.001). Negative correlations were observed between minutes played and absolute time sprinting (r = -0.698, p = 0.037) and distance covered sprinting (r = -0.689, p = 0.040). Results indicate that additional minutes played during the postseason were primarily performed at lower intensity thresholds, suggesting running performance during postseason competitions may be compromised with greater playing time in intercollegiate women`s soccer.